The mediating role of early maladaptive schemas on the relationship between illness perception and pain coping strategies among adolescents diagnosed with migraine - Kayar, Ozan; Altinoğlu Dikmeer, İlkiz; Güler Aksu, Gülen; Toros, Fevziye; Özge, Aynur (Frontiers in Neurology, 2023)
Objective: To examine the mediating role of early maladaptive schemas on the relationship between illness-related perceptions and pain coping strategies among adolescents diagnosed with migraine. Material and methods: 134 adolescents (aged between 12-18) with migraine with and without aura participated in the study. The Illness Perception Questionnaire, Pain Coping Questionnaire, and Early Maladaptive Schema Questionnaires Set for Children and Adolescents were used. Results: The intensity of using desperate ways of coping with pain is higher among adolescents who perceive migraine as a chronic disease (β = 0.199, p < 0.05) even they have episodic attacks, and who have higher levels of coherency in understanding the illness (β = 0.256, p < 0.01). Full mediations of over-vigilance/ inhibition and impaired autonomy/ performance schema domains on these relations were observed. A second finding was about the increases in negative cognitive (β = 0.199, p < 0.05) and emotional (β = 0.280, p < 0.01) representations related to the consequences of the illness leading to an increase in uncontrolled and frequent use of analgesic drugs where partial mediating role of over-vigilance/ inhibition schema domain on this correlation is observed. The perceptions about the negative and serious consequences of the migraine are related both to the self-active behaviors (β = 0.181, p < 0.05) and to conscious cognitive attempts (β = 0.207, p < 0.05) as effective coping strategies, which is an unexpected finding. Disconnection/ rejection schema domain had a full mediation role on both relations. Conclusion: The results suggest that early maladaptive schemas are essential factors to affect the migraine coping processes of adolescents.